2-Methoxy-5((3, 4, 5-trimethosyphenyl)seleninyl) phenol reverses EGF-induced cell migration and invasion through down-regulation of MDM2 in breast cancer cell lines. Issue 4 (3rd April 2019) - Zheng, Dayong; Chang, Xing; Liu, Yang; Xu, Jingwen; Gou, Wenfeng; Li, Zengqiang; Zuo, Daiying; Zhang, Weige; Wu, Yingliang
ABSTRACT: 2-Methoxy-5((3, 4, 5-trimethosyphenyl)seleninyl) phenol (SQ), a novel synthesized combretastatin A-4 (CA-4) analogue, is identified as a microtubule inhibitor and has been shown to exert anticancer activity in breast cancer cells. Here, we found that SQ reversed epidermal growth factor (EGF)-induced motility and invasion in breast cancer cell lines by the in vitro Wound healing and Transwell assay. Further studies showed that SQ treatment resulted in inhibitory alteration of EGF-stimulated epithelial-to-mesenchymal transition (EMT) and MMP-2 activity. What is more, SQ significantly inhibited the EGF-induced mouse double minute 2- (MDM2) expression and transcription factor Twist1 expression. In addition, compared with the control cells, MDM2 overexpression up-regulated Twist1 expression and dramatically promoted cell migration and invasion, MDM2 under-expression also down-regulated Twist1 expression and suppressed cell motility and invasion. Taken together, our findings suggest that the inhibitory effects of SQ on migration and invasion were related to the suppression of MDM2 and Twist1 signal axis.